DETERMINAN KESEJAHTERAAN MASYARAKAT DESA DALAM SEWINDU DANA DESA - Nurhidayati, Nurhidayati (Faculty of Economics and Business University of Mataram, 2023)
Village Funds have been used, among others, for village infrastructure development activities, community empowerment activities, and also to improve village apparatus services. The scope of this research is the village community in East Java, which is the province that has received the most Village Funds in recent times, but the absolute poverty rate in East Java is the highest in Indonesia. This study aims to analyze the effect of infrastructure development in the village, village services to the community, and community empowerment on community welfare. Valid questionnaire results were obtained from 291 respondents who were analyzed using a structural model. This study proves that village development, community service, and community empowerment affect community welfare. However, the village service variable has the least influence compared to the other variables. The aspect of service to the community which refers to the concept of good governance still really needs to be improved for the welfare of the community, through the provision of services in an accountable and transparent manner and taking into account the needs of the community.